CONGO RIVER: ANALYSIS OF SUSPENDED SEDIMENT FLUX IN A MULTICHANNEL MEGASYSTEM IN CENTRAL AFRICA - Queiroz, Matheus Silveira de; Marinho, Rogério Ribeiro (Ra'e Ga: o Espaço Geográfico em Análise, 2024)
Tropical mega rivers play a crucial role in transferring water and sediment to the oceans. The Congo River is the second largest in the world by volume of water, playing a significant role in the export of fresh water and sediment from the continent to the Atlantic Ocean. This paper aims to analyze the variability of the suspended sediment flux of the Congo River between 2005 and 2018. Suspended Sediment Concentration (SSC), water discharge and water level data were used at the Brazzaville station, which represents 97% of the basin area, and precipitation data for the entire basin. Solid discharge, specific sediment yield and denudation rate of the basin were estimated. The estimated water discharge was 41 268 m³.s-1 for the period between 1947 and 2023, with a bimodal river regime with a flood peak in December and a secondary peak in May. The mean annual SSC estimated for the Congo River was 27.20 mg.L-1. A moderate (r = 0.48) and weak (r = -0.26) correlation was observed between SSC and precipitation, and SSC and water level, respectively, possibly influenced by the basin's terrain characteristics. During the year, the Congo River transfers 33.66 × 106 ton.year-1 of sediment to the ocean, has a specific sediment yield of 9.62 ton.km-2.year-1 and a very low denudation rate (3.37 mm.ky-1).